Solar Blind Photodetectors Enabled by Nanotextured β-Ga2O3 Films Grown via Oxidation of GaAs Substrates - Dewyani Patil-Chaudhari; Matthew Ombaba; Jin Yong Oh; Howard Mao; Kyle H. Montgomery; Andrew Lange; Subhash Mahajan; Jerry M. Woodall; M. Saif Islam (IEEE Photonics Journal, 2017)
A simple and inexpensive method for growing Ga2O3 using GaAs wafers is demonstrated. Si-doped GaAs wafers are heated to 1050 °C in a horizontal tube furnace in both argon and air ambients in order to convert their surfaces to β-Ga2O3. The β-Ga2O3 films are characterized using scanning electron micrograph, energy-dispersive X-ray spectroscopy, and X-ray diffraction. They are also used to fabricate solar blind photodetectors. The devices, which had nanotextured surfaces, exhibited a high sensitivity to ultraviolet (UV) illumination due in part to large surface areas. Furthermore, the films have coherent interfaces with the substrate, which leads to a robust device with high resistance to thermo-mechanical stress. The photoconductance of the β-Ga2O3 films is found to increase by more than three orders of magnitude under 270 nm ultraviolet illumination with respect to the dark current. The fabricated device shows a responsivity of ∼292 mA/W at this wavelength.